Quality of primary care delivered to children with asthma in South London before the introduction of integrated child focused care model: a population cohort study of primary care records. (November 2021) - Cecil, Elizabeth; Newham, James; Lingam, Raghu; Wolfe, Ingrid
Abstract: Background: Asthma is one condition being evaluated in a randomised control trial (RCT) of the Children and Young People's Health Partnership (CYPHP) model of care across two boroughs in South London. The integrated, specialist nurse lead service aims to deliver focused, age appropriate, good quality care to improve child health, within an ethnically diverse and deprived population. Providing good quality, evidence-based care is vital to keep children with asthma healthy. This study aimed to determine the quality of asthma care provided to children in primary care before the introduction of CYPHP in May, 2018. Methods: We examined primary care health records of children registered within GP practices in Southwark and Lambeth. We identified children aged 5–15 years between April 1, 2014, and March 31, 2018, with asthma by a coded asthma diagnosis or three or more asthma medications in a 12-month period, and with more than 400 days of continuous GP registration after their asthma was identified. Child asthma quality measures were determined from guidelines and published literature, as follows: children aged 5 years and older with asthma have a personalised action plan; an annual asthma review; asthma control monitored at review; documented height at review; and a prescribed spacer device (which optimises medication delivery). Findings: Of the 7995 children identified with asthma, 44% (n=3508) were from the most deprived fifth of the national population. 36% (n=2868) had a coded annual asthma review record, and 15% (n=1219) had a personalised asthma action plan. Of the 2868 children with a coded annual review, 98% (n=2806) had evidence of asthma control being monitored, while only 2% (n=70) had a coded height documented. 80% (n=6381) had ever been prescribed a spacer. Interpretation: Coding of primary care quality measures for child asthma was poor before the CYPHP service. This finding does not mean that the care was not provided, because information could have been recorded as uncoded text. An audit of primary care records is needed to determine the uncoded care provided. Prescription data are complete for the period a child is registered at a given practice. The fact that 20% of children were never prescribed a spacer needs further investigation. Funding: Guy's and St Thomas' Charity.